2015
DOI: 10.1016/j.paid.2015.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Sense of direction: General factor saturation and associations with the Big-Five traits

Abstract: a b s t r a c tThe ability to locate and orient ourselves with respect to environmental space is known as sense of direction ("SOD"). While there is considerable evidence for the predictive utility of self-report measures of this psychological construct, relatively little research has investigated the psychometric properties of the self-report scale by which it is most commonly measured -the Santa Barbara Sense of Direction scale (SBSOD, Hegarty et al., 2002) -or the broader personality correlates. The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 26 publications
2
35
1
Order By: Relevance
“… Wyllie and Smith (1996) found that adolescents scoring high in extroversion were more likely to explore the environment and spend their leisure time in places farther from home than their less extrovert counterparts. Condon et al (2015) found a correlation between scores for extroversion and self-reported SOD, and also with other personality traits, such as conscientiousness, intellect, and emotional stability.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“… Wyllie and Smith (1996) found that adolescents scoring high in extroversion were more likely to explore the environment and spend their leisure time in places farther from home than their less extrovert counterparts. Condon et al (2015) found a correlation between scores for extroversion and self-reported SOD, and also with other personality traits, such as conscientiousness, intellect, and emotional stability.…”
Section: Introductionmentioning
confidence: 83%
“…In line with these assumptions the literature supports a relationship between certain personality traits and performance in spatial and WF tasks. Extroversion is one of the personality traits most often studied, and findings indicate that extroverts are more likely to have an exploratory behavior ( Wyllie and Smith, 1996 ), and to score higher for self-reported SOD ( Condon et al, 2015 ), a measure that predicts performance in environment tasks ( Hegarty et al, 2006 ). Wyllie and Smith (1996) found that adolescents scoring high in extroversion were more likely to explore the environment and spend their leisure time in places farther from home than their less extrovert counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Integrators may be good navigators because they are adventurous, and relish the challenge of learning a new environment. Silcton performance has not been related directly to personality factors, but SBSOD scores are related to Openness on the Big 5 personality test, which is a measure of curiosity, ingenuity and adventurousness, and to Extraversion, which measures energy, enthusiasm and approach behavior (Condon et al, 2015).…”
Section: Integrating Route Maps To Form Survey Mapsmentioning
confidence: 99%
“…Moreover, both SA and SOD were found to be significant predictors of spatial learning, i.e., both via video and/or within a virtual environment. Interestingly, Condon et al (2015) showed that some of the variance in SOD scores can be explained by participant conscientiousness. Conscientiousness is the human tendency to plan ahead and think with caution before acting on a given task ( John et al, 2008 ), and relates to rule-based behavior and long-term planning.…”
Section: Introductionmentioning
confidence: 99%
“…The experiment considered occurrence of crossing-avoidance violations, i.e., solutions containing crossed edges, as a measure of ETSP performance. In this study we were interested in whether conscientiousness correlates to variance in SOD scores, as suggested by Condon et al (2015) . Moreover, using Principal Component Analysis, we were interested in whether a formed dimension could be used to predict the occurrence of a cross-avoidance violation; which is a strong indicator of graph optimality.…”
Section: Introductionmentioning
confidence: 99%